E-book store for University of Malaya / Lee Kok Keong - Lee, Kok Keong (2001)
E-Book Store for University of Malaya is a web site application that provides Pekan Buku (official book store in University of Malaya) services on-line to the users. Users can use this service from any location at any times as long as they have network connection and able to access to the internet. This project proposal contains the literature review of the system, methodology of system development, system analysis and system design. These topics are explained in detail in each chapter of this proposal. Literature review chapter explains and discusses in detail about the existing systems and technologies that are available in the market. Methodology chapter is concerning about the software engineering principles and techniques that will be applied in the system development process. The system analysis and system design chapters ore dealing with the proposed system's analysis and design issues. It is hoped that this proposal is useful for users in order to understand the proposed system.